1999
DOI: 10.1074/jbc.274.31.22025
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Import of Plasmid DNA in Digitonin-permeabilized Cells Requires Both Cytoplasmic Factors and Specific DNA Sequences

Abstract: Although much is known about the mechanisms of signal-mediated protein and RNA nuclear import and export, little is understood concerning the nuclear import of plasmid DNA. Plasmids between 4.2 and 14.4 kilobases were specifically labeled using a fluoresceinconjugated peptide nucleic acid clamp. The resulting substrates were capable of gene expression and nuclear localization in microinjected cells in the absence of cell division. To elucidate the requirements for plasmid nuclear import, a digitonin-permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(110 citation statements)
references
References 45 publications
(55 reference statements)
2
107
0
1
Order By: Relevance
“…pEPI-EGFP, pMDysE and pDysE contain the SV40 sequences determined to permit optimal DNA entry through nuclear pores. 52 In conclusion, branched 2 kDa PEI was less toxic in PEI adenofection than branched 25 kDa PEI or linear 22 kDa PEI. The adenovirus was necessary to transfect plasmids of 12 kb or more in primary human myoblasts.…”
Section: Figure 4 Expression Of Adenoviral Proteins In Cells After Pementioning
confidence: 82%
“…pEPI-EGFP, pMDysE and pDysE contain the SV40 sequences determined to permit optimal DNA entry through nuclear pores. 52 In conclusion, branched 2 kDa PEI was less toxic in PEI adenofection than branched 25 kDa PEI or linear 22 kDa PEI. The adenovirus was necessary to transfect plasmids of 12 kb or more in primary human myoblasts.…”
Section: Figure 4 Expression Of Adenoviral Proteins In Cells After Pementioning
confidence: 82%
“…Thus, the complex is recognized through the NLS by the protein import machinery and is thereby targeted to the nucleus (2). Indeed, in experiments using digitonin-permeabilized HeLa cells, we have shown recently that nuclear import of plasmids can occur only when both nuclear extract and recombinant importinα, importinβ, and RAN are provided; neither nuclear extract alone nor the purified NLS-import machinery proteins alone can suffice (17). Of the 372 bp in the SV40 origin/promoter region, the enhancer contains the most number of consensus binding sites for such proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have subsequently shown that nuclear import of plasmid DNA is sequence dependent, requires karyopherins (importins) and the small GTPase RAN, and occurs through the nuclear pore complex (NPC). [14][15][16][17][18] In our model of plasmid nuclear import, we propose that transcription factors present in the cytoplasm bind to the DTS and coat the plasmid with nuclear localization sequences (NLSs) that utilize importins to cross the NPC, which regulates the nucleocytoplasmic shuttling of macromolecules during interphase. [19][20][21] We have also developed a tissue-specific DTS, utilizing the smooth muscle g-actin (SMGA) promoter, that mediates nuclear import of pDNA specifically in smooth muscle cells (SMCs).…”
Section: Introductionmentioning
confidence: 99%